Money Demand, Bank Credit, and Economic Performance in Former Socialist Economies - Kumar, Manmohan (IMF Working Papers; Working Paper ;, 1994)
This paper examines factors determining the allocation of bank credit to the enterprise sector, and the implications of this allocation for aggregate supply and macro-economic performance, in the former socialist economies. It first develops a model to explain how changes in demand for money by the household sector directly influence the availability of working capital, which in turn determines aggregate output and employment. It then examines factors influencing the allocation of bank credit between enterprises and other borrowers, in particular the government. Finally, the paper discusses relative merits of bank finance and equity capital in financing medium- and long-term investment, and constraints on the development of efficient equity markets.